2018
DOI: 10.3390/ijerph16010027
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Irrational Use of Antibiotics in Europe

Abstract: The unnecessary use of antibiotics and concomitant rapid growth of antibiotic resistance (ABR) is a widely acknowledged threat to global health, development, and sustainability. While the underlying cause of ABR is undoubtedly the overall volume of antibiotic use in general, irrational antibiotic use, which is influenced by several interrelated factors, is a major contributory factor. Here, we aimed to present and describe selected main drivers of irrational use of antibiotics in Europe. We performed a broad s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
198
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(248 citation statements)
references
References 45 publications
8
198
0
14
Order By: Relevance
“…However, infection prevention and control measures are crucial in order to reduce the incidence of infections and, therefore, reduce the need for antibiotics (40)(41)(42). Besides, the non-involvement of laboratory investigations in disease diagnosis prior to antimicrobial further fuels inappropriate use of antimicrobials, which may subsequently lead to the development and spread of AMR (43,44), which definitely is a big challenge in Ethiopia. Despite the frequent use of antimicrobials by smallholder farmers to maintain good livestock health and production in the studied areas, there was overall poor knowledge about the purpose of antibiotics and their proper use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, infection prevention and control measures are crucial in order to reduce the incidence of infections and, therefore, reduce the need for antibiotics (40)(41)(42). Besides, the non-involvement of laboratory investigations in disease diagnosis prior to antimicrobial further fuels inappropriate use of antimicrobials, which may subsequently lead to the development and spread of AMR (43,44), which definitely is a big challenge in Ethiopia. Despite the frequent use of antimicrobials by smallholder farmers to maintain good livestock health and production in the studied areas, there was overall poor knowledge about the purpose of antibiotics and their proper use.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the education barrier, limited professional supervision can also have an impact on a farmer's practice as reflected in the pastoral production system. Wrong public perception, attitudes, and beliefs about antibiotics are strong determinants of medically irrational use of antibiotics (43). It has been suggested that increasing knowledge and awareness about antibiotics and antibiotic resistance are key components of rational antibiotic use in human medicine (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance has been emerging worldwide . Patient behaviour, treatment adherence, leftover antibiotics and drug waste should be identified as potential targets for restraining antibiotic resistance, and these may be of greatest interest in primary care, outpatient setting or for infections with great prevalence . Considering the latter, it is estimated that 50% of the world's population will be infected with Helicobacter pylori .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is well‐established that patient compliance is inversely related to the number of drugs that the patient it taking . Previous research indicates that leftover antibiotics may contribute to inappropriate antibiotic consumption hence further promoting antibiotic resistance . Drug waste may also contribute to antibiotic resistance and raise healthcare cost .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation